Florida's Nonnative Herpetofauna: Veiled Chameleon (Chamaeleo calyptratus), Oustalet’s Chameleon (Furcifer oustaleti), and Panther Chameleon (Furcifer pardalis) - Max Maddox; Karissa Beloyan; Natalie M. Claunch; Steve A. Johnson (EDIS)
This publication is one in a series of UF/IFAS numbered publications summarizing general knowledge about Florida's introduced reptiles.